Gigitiruan jembatan adesif sebagai perawatan alternatif pada kasus kehilangan satu gigi Adhesive bridge as alternative treatment to replace one missing teeth - Christie Rizki; Deddy Firman; Aprillia Adenan (DiscoverSys Inc., 2012)
Adhesive bridge is a fixed partial denture that consisted of pontic and cast metal framework retainer that cementedto abutment teeth by means of adhesive cement, used acid etch technique. Adhesive bridge can be used to replaceone or two anterior or posterior teeth. This case report focused on the making of adhesive bridge in anterior andposterior single missing tooth. By minimal preparation and unanesthesied teeth, patient satisfaction could beachieved. Treatment should be done as patient needed with the adequate clinical technique and specific materialmanipulation.